The Prevalence of Sexual Victimization in Children and Adolescents of Indigenous and Non-Indigenous Peoples in Chile. - Pinto-Cortez, Cristián; Guerra, Cristóbal; Miranda, Jenniffer K.; Varela, Jorge; Álvarez-Lister, Soledad (Journal of Child Sexual Abuse, 2025)
Chilean studies show high levels of sexual victimization among adolescents. Despite this, there is little research exploring differences between adolescents belonging to Indigenous communities and the general population. This is relevant because 12.8% of the Chilean population is from an Indigenous community. In this study, data from 13,385 adolescents all over the country (15.8% indigenous) were analyzed. The prevalence of seven forms of sexual victimization throughout life was examined. Adolescents from Indigenous communities presented a higher prevalence of statutory rape, sexual abuse by an unknown adult, sexual abuse by a known adult, and rape although the effect size was small in all cases and the difference in prevalence rates was less than 2.5%. The results suggest that although attention should be paid to these differences, factors that may contribute to the vulnerability of adolescents from both groups should be explored. For example, in this study, adolescents from Indigenous communities came from a lower income segment compared to their non-Indigenous peers. In Chile, extreme poverty is associated with vulnerability factors for abuse in adolescents of any ethnic origin, so public programs and policies should consider not only ethnicity, but also other factors such as gender, socioeconomic level, and social support network.